Duch liturgii – głos ludzki (Fragment Opera omnia Josepha Ratzingera, t. 11, Teologia liturgii. Sakramentalne podstawy życia chrześcijańskiego, tłum. W. Szymona OP) - RATZINGER, Joseph (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
In the Liturgy of the Logos, of the Eternal Word, the word and thus the human voice have an essential role to play. First there is the oratio, the priestly mode of prayer, in which the priest, in the name of the whole community, speaks through Christ, in the Holy Spirit, to the Father. Then there are the various forms of proclamation: the readings, the Gospel (solemnly sung at High Mass), and the homily, which in the strict sense is reserved to the bishop and then to the priest and deacon as well. Then there is the response to the Word [Ant-Wort], by which the assembled congregation takes up and accepts the Word. This structure of Word and response, which is essential to the liturgy, is modeled on the basic structure of the process of divine revelation, in which Word and response, the speech of God and the receptive hearing of the Bride, the Church, go together. In the liturgy, the response has different forms. For example, there is the acclamation, which is of great importance in the world of ancient law. The responsive acclamation confirms the arrival of the Word and makes the process of revelation, of God’s giving of himself in the Word, at last complete. The Amen, the Alleluia, and the Et cum spiritu tuo, and so on, are all part of this. One of the important results of the liturgical renewal is the fact that the people really do again respond in the acclamation and do not have to leave it to a representative, the altar server. God, the Revealer, did not want to stay as solus Deus, solus Christus (God alone, Christ alone). No, he wanted to create a Body for himself, to find a Bride – he sought a response. It was really for her that the Word went forth. Alongside the acclamation are the various forms of meditative appropriation of the Word, especially in the singing of psalms (but also in hymns). Then there is the “new song,” the great song the Church sings as she goes off toward the music of the New Heaven and the New Earth. This explains why, in addition to congregational singing, Christian liturgy of its very nature finds a suitable place for the choir and for the instruments. We are realizing more and more clearly that silence is part of the liturgy. We respond, by singing and praying, to the God who addresses us, but the greater mystery, which no word can express calls us to remain silent at moments such as that after the homily, during the Preparation of the Gifts, during the Consecration, and after Communion. Shared silence becomes shared prayer, indeed shared action, a journey out of our everyday life toward the Lord, toward merging our time with his own. Liturgical education ought to regard it as its duty to facilitate this inner process, so that in the common experience of silence the inner process becomes a truly liturgical event and the silence is filled with content. There is also a silence that is part of the liturgical action, not an interruption, namely, the silent prayers of the priest. Those who hold a sociological or activistic view of the priest’s duties in the Mass frown upon these prayers, and, whenever possible, they leave them out. The priest is defined in narrowly sociological and functionalistic way as the “presider” at the liturgical celebration, which is thought of as a kind of meeting. If that is what he is, then, of course, for the sake of the meeting, he has to be in action all the time. But the priest’s duties in the Mass are much more than a matter of chairing a meeting. The priest presides over an encounter with the living God and as a person who is on his way to God. The silent prayers of the priest invite him to make his task truly personal, so that he may give his whole self to the Lord. The priest should pray silently with real recollection and devotion, conscious of his responsibility to proclaim the Gospel aright, conscious, too, of the need which that entails for a purification of lips and heart. When the priest does this, he shows the congregation the dignity and grandeur of the Gospel and helps them understand how tremendous it is that God’s Word should come into our midst. The priest’s prayer creates reverence and a space for hearing the Word. Again, liturgical education is necessary if the priest’s prayer is to be understood and the people are not only to stand up physically but also to rise up spiritually and open the ears of their hearts to the Gospel. Old prayer books contain, alongside a lot of kitsch, much that is a valuable resource for prayer, much that has grown out of deep interior experience and can again become today a school for prayer. What St. Paul says in the epistle to Romans – that we do not know how to pray as we ought (Rom 8:26) – applies even more to us today. So often we are without words in our encounter with God. The Holy Spirit does indeed teach us to pray; he does indeed give us the words, as St. Paul says; but he also uses human meditation. The prayers that have risen up from the hearts of believers under the guidance of the Holy Spirit are a school, provided us by the Holy Spirit, that will slowly open our mute mouths and help us to learn how to pray and fill the silence. Extract from Jospeh Ratzinger’s Der Geist der Liturgie. Eine Einführung (Herder Verlag, Freiburg 2000), reprinted from: Jospeh Ratzinger, Teologia liturgii. Sakramentalne podstawy życia chrześcijańskiego, trans. W. Szymona, OP, Wydawnictwo KUL, Lublin 2012, pp. 163-170 (Volume XI of the Polish Edition of Joseph Ratzinger’s Opera omnia, ed. K. Góźdź and M. Górecka). For the English edition see: Joseph Cardinal Ratzinger, The Spirit of the Liturgy, trans. J. Saward, Ignatius Press, San Francisco 2000.